2021
DOI: 10.3390/ijerph18137179
|View full text |Cite
|
Sign up to set email alerts
|

Shame and STIs: An Exploration of Emerging Adult Students’ Felt Shame and Stigma towards Getting Tested for and Disclosing Sexually Transmitted Infections

Abstract: Emerging adulthood is identified as a time of identity exploration, during which emerging adults (EAs) may engage in sexual exploration and risky behaviors, potentially resulting in the contraction of a sexually transmitted infection (STI). Many EAs, do not disclose their status to partners or those who can provide social support, like parents. Nor do they often get tested. This may be due to the changing status of stigma surrounding STIs. This study examines traditional measures of the stigma/shame of STI dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Studies have shown a positive correlation between increasing knowledge of how STI infections are transmitted and a decrease in levels of stigma. 9,21 However, it remains unclear if consumer-based methods of STI screening, even if including an educational component, will influence testing behavior and overcome the associated stigmas. Although consumer-based methods may address privacy and reduce judgment concerns from healthcare providers, it may not address the multilayered stigmas influencing screening.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have shown a positive correlation between increasing knowledge of how STI infections are transmitted and a decrease in levels of stigma. 9,21 However, it remains unclear if consumer-based methods of STI screening, even if including an educational component, will influence testing behavior and overcome the associated stigmas. Although consumer-based methods may address privacy and reduce judgment concerns from healthcare providers, it may not address the multilayered stigmas influencing screening.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true related to STIs, where a complex web of individual, social, and systemic factors are known barriers to STI screening among women, especially among adolescent and young adult populations 6,8 . Individual-level perceptions, such as STI-related shame, are a commonly reported self-stigma experienced by people diagnosed with an STI 6,9,10 . Sexually transmitted infection diagnoses are associated with feelings of shame, which may cause adverse psychosocial distress, including embarrassment, fear of judgment, guilt, and isolation 6,10,11 .…”
mentioning
confidence: 99%
See 3 more Smart Citations